Catastrophic Failure of Reverse Shoulder Arthroplasty from a Broken Screw: A Case Report. Issue 3 (28th July 2020) - Ramirez, Miguel A; Lu, Yining; Schaver, Andrew
Abstract : Case: A 63-year-old woman presented with pain and limited range of motion 2 years after undergoing reverse shoulder arthroplasty (RSA). She underwent revision RSA for catastrophic implant failure caused by central screw breakage, subsequent polyethylene wear, and glenosphere loosening, and achieved excellent outcomes. Conclusion: This is a unique case of a salvage procedure with satisfactory outcomes for a rare complication of RSA. It demonstrates the importance of clinical vigilance notwithstanding the absence of radiographic abnormalities in long-term monitoring of patient implant failure.